Patterns of Birth Weight in Rural Tanjungsari, West-Java - Anna Alisjahbana; Ali Usman; S. Tanuwidjaja; R. Peeters; A. Meheus (Paediatrica Indonesiana, 1995)
Few population studies on birth weight distribution are available in Indonesia. This report is the result of a cohort of pregnant women who were followed from early pregnancy through delivery until the child is two years of age in a rural area Tanjungsari, about 45 km from Bandung. The infants were born between January 1, 1988 -December 31, 1989. A total of 3818liveborn infants were available for analysis. The birthweight was grouped into low birth weight (<2500 g), deficient birth weight (2500-<3000 g), and favorable birthweight (>3000 g). The percentages were 13.9, 45.5 and 40.6 percent, respectively. The percentage of favorable birth weight in this study was lower compared with that in developed countries, it was even lower compared with other studies in Indonesia. The Tanjungsari has shown that the pattern of birth weight of live born infants have a distinct relationship to survival. Taken into consideration that most of low birth weight infants died in the neonatal period, improvement in birth weight may result in decline in infant mortality.